Public-Private Partnerships (PPPs) in Infrastructure Development: A Bibliometric Review - Judijanto, Loso; Mas’ut, Mas’ut; Andiani, Paramita (West Science Social and Humanities Studies, 2025)
This study presents a comprehensive bibliometric analysis of scholarly literature on Public-Private Partnerships (PPPs) in infrastructure development, using data retrieved from the Scopus database and analyzed through VOSviewer. The objective is to map the intellectual structure, thematic evolution, and global collaboration patterns within the field. The results reveal three major research clusters: (1) infrastructure governance and economic development, (2) financial and managerial structuring, and (3) sustainability and risk assessment. Temporal overlay visualization indicates a shift from foundational themes toward applied concerns such as project finance, policy integration, and sector-specific applications including public health and agriculture. Density mapping shows high research concentration on infrastructure provision, sustainable development, and risk management. Co-authorship and country-level analyses highlight the dominance of scholars and institutions from the United States, United Kingdom, China, and other emerging economies, reflecting a globally interconnected research landscape. This review offers valuable insights into the progression and diversification of PPP research and suggests future directions focused on interdisciplinary integration, social impact, and inclusive infrastructure delivery.